Efeito de condicionantes ambientais no incremento diamétrico de Peltogyne gracilipes Ducke (Leguminosae) em área de ecótono no norte de Roraima - Santos, Raylanne de Lima (2019)
The vulnerability of the Amazon rainforest to dry events is becoming increasingly evident, especially in areas with climatic seasonality. Interest in this theme has been increasing due to concerns related to changes in tropical forests, especially regarding climate variations and their effects on carbon accumulation. In order to verify the behavior of tree individuals and to understand the mechanisms that influence carbon accumulation in trees, this study aimed to determine the intra-annual variations in the diameter increment of Peltogyne gracilipes (Leguminosae) along a topographic gradient located in an area of ecotonal forests of northern Roraima. P. gracilipes is a bioindicator species of local vegetation, featuring monodominance in some environments. The abundance of the species is strongly influenced by environmental characteristics and is associated with edaphic factors (soils with high aluminum content) and lower altitude areas (seasonally flooded). We used dendrometers bands to evaluate intra-annual variations in diameter increment and to verify the effect of environmental conditions (canopy illumination index, soil, altitude, abundance and precipitation) in permanent plots of PPBio located at Maracá Ecological Station (Amajarí, RR). Individuals were monitored bimonthly over one year (March/2018 - March/2019). Of the 158 individuals observed, 88% had a mean cumulative diameter growth of 3.4 mm year-1. Intra-annual variation in diameter was observed, with decreased in increment from the beginning of the dry season, reaching an average reduction of 0.71 mm in ~ 81% of individuals in the last measurement (end of dry season). Precipitation explained 68% of the variations in the diameter increment of the species in the model tested It was concluded that rainfall determined intra-annual diameter variations of P. gracilipes in ecotone area in northern Roraima, regardless of altitude, light and soil conditions.